2016
DOI: 10.1103/physrevb.94.155117
|View full text |Cite
|
Sign up to set email alerts
|

X-ray absorption and emission spectroscopy study of Mn and Co valence and spin states inTbMn1xCoxO3

Abstract: Abstract.The valence and spin state evolution of Mn and Co on TbMn 1-x Co x O 3 series is precisely determined by means of soft and hard x-ray absorption spectroscopy (XAS) and Kβ x-ray emission spectroscopy (XES). Our results show the change from Mn 3+ to Mn 4+ both high-spin (HS) together with the evolution from Co 2+ HS to Co 3+ low-spin (LS) with increasing x. In addition, high energy resolution XAS spectra on the K pre-edge region are interpreted in terms of the strong charge transfer and hybridization ef… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 39 publications
2
16
0
Order By: Relevance
“…the intensity of p2 decreases with decreasing the number of empty states in 3d orbitals. In our case the intensity of p2 feature increases with doping, particularly for x=1 sample containing formally Mn 4+ ions, which is in agreement with interpretation suggested by Cuartero et al 26 In order to obtain more quantitative understanding of the pre-edge doping evolution we estimated the p2 intensity, taken as the maximum from the experimental data (Fig.5a) as well as maximum and area from the data fits (see the supplement 15 and supplementary Fig.5). In Fig.5a we also show the dependence of the probability of finding different number of Mn 4+ ions as neighbors of given absorber (Mn ion) calculated from a binomial distribution.…”
Section: A Xanessupporting
confidence: 90%
See 2 more Smart Citations
“…the intensity of p2 decreases with decreasing the number of empty states in 3d orbitals. In our case the intensity of p2 feature increases with doping, particularly for x=1 sample containing formally Mn 4+ ions, which is in agreement with interpretation suggested by Cuartero et al 26 In order to obtain more quantitative understanding of the pre-edge doping evolution we estimated the p2 intensity, taken as the maximum from the experimental data (Fig.5a) as well as maximum and area from the data fits (see the supplement 15 and supplementary Fig.5). In Fig.5a we also show the dependence of the probability of finding different number of Mn 4+ ions as neighbors of given absorber (Mn ion) calculated from a binomial distribution.…”
Section: A Xanessupporting
confidence: 90%
“…from 1s to the 4p character of the 3d-band of the excited ion for geometry with broken inversion symmetry and non-local i.e. to a 3d states of neighboring metal sites through the oxygen mediated intersite hybridization Mn(4p)-O(2p)-Mn'(3d) 21,26 . It has been suggested that this non-local contribution appears at a higher energy since such a final state is also more delocalized and thus it is less affected by the core hole potential 21,26 .…”
Section: A Xanesmentioning
confidence: 99%
See 1 more Smart Citation
“…This result agrees with the findings using x-ray absorption near edge structure (XANES) spectroscopy in related double perovskites. 21,26 b. Magnetic ordering in Ho 2 CoMnO 6 and Tm 2 CoMnO 6 .…”
Section: Methodsmentioning
confidence: 99%
“…Here, the energy position of the absorption edge (E 0 ) is taken at the maximum of the derivative of the normalized f signal. Co 3+ in an octahedral oxygen environment [42] is about 2.6 eV, this means that the charge segregation between Co1 and Co2 sites is about 0.6 ± 0.1 electron. The unpolarized XANES spectra of Co1 and Co2 sites compare quite well with those of La 2 CoO 4.2 and LaSrCoO 3.99 , respectively in what regards the energy position of the absorption edge, which results in a charge difference between the nominal average Co oxidation states of 0.42 ± 0.1 electron, as reported in the Experimental section.…”
Section: B Theoretical Model and Analysismentioning
confidence: 96%